The native English teachers' expectations in teaching EFL students - Tgk Maya Silviyanti; Sofyan A. Gani; Dara Junita (Studies in English Language and Education, 2021)
Research into students’ expectations towards native English speakers or teachers has been commonly investigated for years, yet the significant exploration of native teachers’ perceptions towards their foreign students are rarely examined. This study tries to find out the Native English Speaker Teachers’ (NESTs) expectations in teaching English as a foreign language (EFL) students. The data were compared with Gani et al.’s (2015) previous study of EFL learners’ expectations toward their native teachers. The participants in this study were two native English teachers who are currently working at Universitas Syiah Kuala, Banda Aceh, Indonesia. The interview was selected as the instrument to collect the data. The interview guide was designed and formulated based on a list of questionnaires that originated from Wu and Ke (2009). The interview with each teacher was recorded and the results were transcribed. The findings show that NESTs generally have similar expectations with the EFL students regarding speaking rate, learning environment, accent preferences, and assignments. However, diverse expectations occurred on the subject of syllabus design, grading system, grammatical correction, and pronunciation articulation. The results are further discussed in the paper. Consequently, the findings of this study can be used as a reference for both native teachers and EFL students in fulfilling the goal of learning in the classroom.